IOT BASED AGRICULTURAL FEATURES FOR SUPPORTING FARMERS - AYAN GHOSH (International Journal of Innovations in Engineering Research and Technology, 2021)
Agriculture sector has an important role in the country’s economy. A steep decline in this sector is observed as the crop loss and the suicide rate of the farmers are increasing day by day. The young population of the country is disinterested in this profession and the methods used for cultivation are predominantly unscientific. The climatic conditions and the soil components have drastically changed, thus olden methods of cultivation are not very effective. The soil wants to be clinically tested to find the NPK (nitrogen, phosphorus, and potassium) values. Other parameters considered are temperature, humidity, soil moisture, and soil pH which are obtained in real-time from the sensors. This proposed system uses many sensors to detect the current soil condition and the need of fertilizer or water giving the farmer a comfortable zone to cultivate the crop. The use of these new technologies makes a change from traditional methods to precision farming. Crop loss can be reduced thereby increasing the profit of the farmers. The system is developed as a web application where the farmers can easily check out the suitable crop right into his smartphone. The proposed system is very beneficial for the farmers to take a valuable decision. Thus more young populations with low experience can engage in farming and increase the economic growth of the country.